Risk Assessment of Steel Structure Engineering Cost using Multi-Criteria Decision-Making Approach under Uncertainty - Bijun Ni (Neutrosophic Sets and Systems)
Choosing options with complex, ambiguous, and contradicting criteria is a common challenge for decision-makers. To choose the optimal option, they typically use multicriteria decision-making techniques, in which specialists manage the relative importance of conflicting tangible and intangible criteria to identify and evaluate possible courses of action. Making decisions involves one or more people selecting the best option from a range of potential options. This study proposes multi-criteria decision making (MCDM) method to compute the criteria weights are rank the alternatives. The MCDM approach is applied for risk assessment to cost in steel structure engineering. This problem includes many criteria and alternatives. The MCDM method is used under the plithogenic set to deal with uncertainty in the evaluation process. The grey relational analysis (GRA) is an MCDM method used in this study to rank the alternatives. Eight criteria and eight alternatives are gathered to apply the MCDM approach. The sensitivity analysis is conducted in this study.